SEM investigation of polishing composite restorations - Petrović Renata M. (Serbian Medical Society - Dental Section, Belgrade, 2004)
Proper finishing and polishing of composite restaurations are procedures that enhance the quality of restorations and reduce plaque accumulation. The purpose of this study was to evaluate with SEM analysis the effect of different polishing methods and instruments of composite surface after polishing. We used different instruments for finishing and polishing: carbide tungsten burs, diamond fissural burs, steel fissural burs, Lo-Flex Pop On discs, Sof-Lex Pop On discs, Hawe rubber cups, gray rubber cups, green rubber cups, polishing strips, polishing pastes. The results we obtained showed that the most efficient polishing of composite restorations was achieved after treatment with Sof-Lex discs, rubber cups and pastes. Treatment with carbide tungsten burs, was the least effective, producing the lowest smoothness of composite surface.